Diagnostic neuropathology smears - Joseph, Jeffrey T. (Lippincott Williams & Wilkins, 2007)
Provides practical information on how to perform and interpret smears and use smears for diagnostic intraoperative neuropathology. The book covers most aspects of brain biopsies that require intraoperative or "frozen section" diagnosis, including tumors, non-neoplastic lesions, infectious diseases, and metastases to the brain. The author also discusses more general aspects of smears, including their preparation and general interpretation. Emphasis is on the structural information about brain lesions supplied by the technique of smears, as well as the patterns of smears produced by different tumors. More than 200 full-colour illustrations complement the text.